Analisa Prakiraan Kebutuhan Energi Listrik Bandar Udara Sultan Syarif Kasim II Pekanbaru Tahun 2017-2027 Dengan Metode Regresi Linear - Wicaksono, M Arif; Sukma, Dian Yayan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Forecast demand of electrical energy Sultan Syarif Kasim II Pekanbaru years 2017-2027 with linear regression method. Linear regression method used to determine to had forecast or predicting the value of one variable in conjuction with other variables. On method is divided into 3 (three) segments services available in the Sultan Syarif Kasim II Pekanbaru, namely aeronautics, non-aeronautics and cargo segments services. Forecast demand of electrical energy influenced by electric energy consumption. The data used history data for 6 (six) years, namely from year 2011 until 2016. Master plan Sultan Syarif Kasim II Pekanbaru City Province of Riau will further developing the airport and necessary forecast demand of electrical energy. The percentage of growth forecast demand of electrical energy Sultan Syarif Kasim II Pekanbaru is 11,15% per-years will total needs 10.842.880,19 kWh in 2017 and increased until 2027 is 35.376.553,72 kWh.Keywords: electrical energy, linear regression, consumption of electricity, demand of electrical energy